Sincronização e continuidade em um problema parabólico governado pelo p-Laplaciano - Pereira, Ana Claudia (2009)
In this work we study a reaction diffusion problem governed by the p-laplacian with p > 2 and we analyze properties of the continuity of the set of equilibria with respect to the diffusion parameter. We also consider coupled non-identical systems and we obtain properties about the synchronicity. Moreover we prove the convergence of the attractors with respect to the coupling parameter.